REFORMULASI PEMBELAJARAN FILSAFAT ISLAM PRAKTIS DI ERA TEKNOLOGI INFORMASI - Badrul Munir Chair; Moh. Hadi Subowo (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Practical philosophy is one of the philosophical patterns to bring philosophy closer to everyday life. In Islamic philosophy, the practical philosophy is called a wisdom 'Amali, namely philosophy about human behavior or efforts. Unfortunately, the discussion of practical philosophy lately does not get the ideal portion, so philosophy seems to be a realm that discusses the theoretical things and gives rise to the impression that the philosophy is very up and merely theoretical. The presence of philosophical theories that can provide a way out of various modern human problems is needed, especially in the information technology era with multiple issues and complexity. With these considerations, this study will analyze the reformulation of practical Islamic philosophy in the age of information technology. This type of research is qualitative research by applying the library study method. This study indicates that in the treasure of Islamic philosophy, the emphasis on the importance of practical philosophy and the practical philosophy description is stated in almost all Islamic philosophical figures, both classic and medieval periods. Among the Islamic philosophers that discuss the problem of human life relevant to modern human life is Al-Kindi (Al-Hilah lil-Daf Al-Ahzan), Al-Farabi (Risalah Tanbih ila al-Sabili al-Sa'adah), and Al-Ghazali (Mizan Al-Amal and Al-Munkidz min al-Dhalal). While the reformulation model and development of practical Islamic philosophy learning can be done by introducing practical Islamic philosophy, sorting out the concept of practical philosophy relevant to people's lives in the era of information technology, and making philosophical interpretations of the achievement of classical Islamic philosophers so that their thinking concepts are applicable to life Today's society.